2020
DOI: 10.1101/2020.01.10.901165
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocean currents promote rare species diversity in protists

Abstract: Oceans host communities of plankton composed of relatively few abundant species and many rare species. The number of rare protists species in these communities, as estimated in metagenomic studies, decays as a steep power law of their abundance. The ecological factors at the origin of this pattern remain elusive. We propose that oceanic currents affect biodiversity patterns of rare species. To test this hypothesis, we introduce a spatially-explicit coalescence model able to reconstruct the species diversity in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…It is worth noting that this enhanced vertical connectivity could promote the movement of taxa between various water layers, providing ecological opportunities that drive species adaption and diversification (Wellborn and Langerhans, 2015). This is supported by a further study that confirmed a steep increase in the number of observed species within a given sample size in the presence of chaotic advection (Martin et al, 2020).…”
Section: Seamount Effect Along the Vertical Gradientmentioning
confidence: 64%
“…It is worth noting that this enhanced vertical connectivity could promote the movement of taxa between various water layers, providing ecological opportunities that drive species adaption and diversification (Wellborn and Langerhans, 2015). This is supported by a further study that confirmed a steep increase in the number of observed species within a given sample size in the presence of chaotic advection (Martin et al, 2020).…”
Section: Seamount Effect Along the Vertical Gradientmentioning
confidence: 64%
“…The experimental evolution of dispersal and movement in the freshwater ciliate Tetrahymena illustrated an increase in individual movement velocity and overall dispersal rates of populations at the margins of their distribution range over time (Fronhofer and Altermatt, 2015). Soft hydrographic barriers might cause populations to experience selection sufficiently strong on either side that speciation may take place, although they do not inhibit dispersal completely (Martín et al, 2020). Actually, individual populations might be more isolated than currently accepted as patterns of dispersal and connectivity could be highly structured (McManus and Woodson, 2012).…”
Section: Potential Causes For Geographic Patterns and Diversificationmentioning
confidence: 99%
“…Abundant species usually contribute a signi cant role in the ecosystem and participate in major biogeochemical processes such as carbon flow and processing of nutrients, whereas rare taxa can be regarded as propagule banks and play minor but non-negligible roles 41,42 . A ubiquitous pattern has been observed across ecosystems whereby many species are rare, and a few species are abundant [20][21][23][24] . This pattern is also found in our research: there was no species classi ed as always abundant in 2015 in Luoma Lake, and the number of conditionally abundant species varied from 1 (0.4%) in 2018 to 8 (4.0%) in 2015.…”
Section: In Uence Of Environmental Selection On Abundant and Rare Phytoplankton Sub-communitiesmentioning
confidence: 99%
“…The rare taxa were observed to be dissimilar and to encompass many more unique species in the three lakes. The rare subcommunities could be inert in one speci c environment [20][21] , but may become abundant taxa upon environmental changes [22][23] . The rare species underwent dramatic changes in Luoma, Nansi and Dongping lakes following from the water diversion project.…”
Section: In Uence Of Environmental Selection On Abundant and Rare Phytoplankton Sub-communitiesmentioning
confidence: 99%
See 1 more Smart Citation